Efektivitas Flipbook Digital Materi Kisah Keteladanan Walisongo untuk Meningkatkan Hasil Belajar Siswa MTsN 1 Jombang - Ummah, Roifatul; Rahmawati, Rina Dian (ANWARUL, 2025)
This research is motivated by students' difficulties in understanding the subject matter of Islamic Cultural History, which is considered complex and abstract, especially in the material on the exemplary stories of Walisongo. Learning media innovations such as digital flipbooks are needed to improve student learning outcomes. This study aims to measure the effectiveness of digital flipbooks in improving student learning outcomes in the material on the exemplary stories of Walisongo. This study uses a quantitative approach with a quasi-experimental design model involving an experimental class (using digital flipbooks) and a control class (conventional learning) with subjects of class IX students of MTsN 1 Jombang. Data collection in this study was in the form of tests. Data analysis in this study used normality tests, homogeneity tests, independent sample t-tests, and normalized N-Gain. Based on the results of the analysis using SPSS version 30, the results of the independent sample t-test showed a sig value (2-tailed) <0.001. The N-Gain test results for the experimental class were 66.3% (quite effective) and the control class was 41.8% (less effective). Based on these two data analyses, it can be concluded that students who use digital flipbooks in learning obtain higher average scores than students who use learning without digital flipbooks. This means that digital flipbook learning media can be an effective alternative used in learning the material on the exemplary stories of Walisongo.